EFFECTS OF NITROGEN AND COPPER FERTILIZATION ON RICE YIELD AND FERTIL- IZER NITROGEN EFFICIENCY: A 15N TRACER STUDY - Choudhury, A T M A; Khanif, Y M (Biological Sciences - PJSIR, 2004)
A greenhouse experiment was conducted at University Putra Malaysia to evaluate the effects of nitrogen (N) and copper (Cu) fertilizations on rice yield and fertilizer N efficiency using 15N tracer technique. Four rates of N (0, 60, 120 and 180 kg N ha-1 and three rates of Cu (0, 5 and 10 kg Cu ha-1) were used in this study. Nitrogen was applied as 15N tracer technique. Four rates of N (0, 60, 120 and 180 kg N ha-1) and three rates of Cu (0, 5 and 10 kg Cu ha-1) were used in this study. Nitrogen was applied as 15N labelled urea. Grain yield increased significantly due to N fertilization up to 120 kg N ha-1. Regression analysis indicated that grain yield response due to N fertilization that was quadratic in nature. Estimated N rate for maximum yield was 158 kg N ha-1. Copper application did not increase grain yield although the soil was deficient in Cu. The 15N atom excess percentage in both grain and straw, and fertilizer N uptake by rice plant increased gradually with increasing N rates. Recovery (%) of fertilizer N was around 40% irrespective of N and Cu rates. The non- significant effect of Cu might be due to higher Cu adsorption in the soil. Plant analysis results indicated that Cu content in the straw was below the critical deficiency level of 6 mg kg-1. These findings indicate that higher rate of Cu fertilizer (above 10 kg Cu ha-1) may be useful in this soil to increase rice yield and fertilizer N efficiency if Cu is applied as basal. Alternately, Cu may be applied as foliar spray on standing crop to avoid Cu adsorption in the soil. Further, research is needed to find out the optimum Cu rate and method of application for this soil.